Filamentous fungi - Hawksworth, D. L.; Kirsop, B. E.; Jong, S. C. (Living resources for biotechnology, 1988)
This volume is an international compilation for biotechnologists of data on the location and use of filamentous fungi. The volume provides details of the location and scope of major culture collections around the world holding fungi; information on how to access their data, administration and safety, identification, culture and media recipes, preservation, patents, specialist services and international organization. The authors are international authorities who have combined with the resource centres to provide a source book for mycologists in industry, research establishments and universities